ANALISIS KAPASITAS RUANG PARKIR OFF STREET DI RUMAH SAKIT JASA KARTINI KOTA TASIKMALAYA - dea amelia, azkia; sumarno, wahyu; defiana, yanti (Jurnal Ilmiah Teknik Sipil, 2024)
Jasa Kartini Hospital is located on Jalan Otto Iskandardinata Tasikmalaya City. Seen during rush hour, the available parking lot often accommodates the number of vehicles that exceed the capacity it should be. Therefore, Jasa Kartini Hospital needs enough parking space to meet the needs of visitors. The purpose of this study was to determine the capacity of off street parking spaces as well as static and dynamic capacities at Jasa Kartini Hospital Tasikmalaya City. This research uses quantitative methods by measuring parking area and taking data on parking volume and parking duration. Then analysis is carried out to obtain results static and dynamic capacity at the location. The results ofthis study can be concluded that the capacity of off street parking spaces of Jasa Kartini Hospital Tasikmalaya City has a land area of 450.83 for motorcycles and 800.54 for cars. The parking volume of motorcycles is 607 vehicles and cars are 348 vehicles. The accumulation of motorcycle parking is 322 vehicles and cars are 88 vehicles. The duration of parking for motorbikes is 577 minutes and cars are 554 minutes. The motorcycle parking index was 156.31% and cars were 237.84%. The static capacity of off street parking spaces at Jasa Kartini Hospital Tasikmalaya City resulted in the number of motorbike parking of 206 SRP while the need for parking spaces was 227 SRP and cars amounted to 37 SRP while the need for parking spaces was 44 SRP. And for the dynamic capacity of motorcycles, the largest occurred on Sunday at 972.74 and the smallest on Thursday at 526.34. The largest dynamic capacity of the car occurred on Wednesday at 583.23 and the smallest occurred on Sunday at 215.50.